TROPICAL FORESTRY POLICY IN INDONESIA: EVALUATING THE INTEGRATION OF SCIENCE, TECHNOLOGY, AND PUBLIC PARTICIPATION - Jemima Reid; David Mayers; Michael Parris (Journal of Selvicoltura Asean, 2026)
Tropical forests in Indonesia are under increasing pressure from deforestation, land-use change, and climate variability, posing significant ecological, economic, and social challenges. Current forestry policies often struggle to balance sustainable management objectives with economic development priorities. The integration of scientific knowledge, technological innovation, and public participation is recognized as a critical pathway to enhancing policy effectiveness and ensuring long-term forest resilience, yet empirical evaluation of this integration remains limited. This study aims to evaluate how Indonesian forestry policies incorporate scientific evidence, technological tools, and stakeholder participation in policy formulation and implementation. The research assesses policy frameworks, governance structures, and stakeholder engagement mechanisms to identify strengths, gaps, and opportunities for improvement. A mixed-methods approach was employed, combining document analysis of national and regional forestry policies, semi-structured interviews with 40 policymakers, forestry experts, and community representatives, and field observations in three major forested regions. Data were analyzed using thematic coding, comparative policy assessment, and descriptive statistics to evaluate the level and effectiveness of integration. Results indicate that policies incorporating technological monitoring systems, participatory decision-making, and scientific assessments achieve higher compliance, adaptive capacity, and stakeholder satisfaction. However, inconsistencies across regions and limited public engagement constrain overall effectiveness. The study concludes that integrative approaches strengthen policy outcomes, but systematic mechanisms for scaling science, technology, and public participation are required to enhance sustainable tropical forestry governance in Indonesia.